RWD 227: Daily doses and duration of gabapentin and pregabalin use for pain management among opioid users below and above 65 years old: trends and patterns - Mohd. Zin, Che Suraya; Alias, Nor Elina; Mohd Kamalul Abrar, Nabil Husaini; Mubarak, Naeem; Ahmad Shah, Mazlila (Elsevier, 2025)
Objectives: Despite the rising use of gabapentinoids, there is limited data on dosing trends, patterns, and duration of use, particularly among elderly populations.This study investigates trends and patterns in the daily doses and duration of gabapentinoid use for pain management among opioid users aged below and above 65 years. Methods: A retrospective cross-sectional study was conducted using prescription data from a tertiary hospital in Malaysia between 2010 and 2020. The study included all gabapentin and pregabalin prescriptions issued to opioid users aged 18 and above for pain management. Descriptive statistics and linear trend analysis were used to evaluate trends in the mean daily doses and days of supply of gabapentin and pregabalin, stratified by age groups (,65 and $65 years). Results: The study analyzed 6,734 prescriptions for 2,338 patients, with 54.3% of patients being female and a mean age of 56.62 years (SD = 14.88). Gabapentin accounted for 91.3% of prescriptions (n=6,148), while pregabalin made up 8.7% (n=586). For gabapentin, the mean daily dose significantly increased over the study period, with the older group ($65 years) experiencing a 237.96% rise (P,0.001), compared to a 110.96% (P,0.001 increase in the younger group (,65 years). For pregabalin, the dose increase was smaller, with the older group experiencing a 49.35% increase (P=0.561), and the younger group seeing a 38.70% rise (P=0.512). The day supply for gabapentin also increased significantly, with the older group showing a 54.1% rise (P,0.001) and the younger group a 76.8% increase (P,0.001). Pregabalin’s day supply increased by 171.7% (P=0.003) for the older group and 116.4% (P=0.002) for the younger group. Conclusions: Gabapentinoids, particularly gabapentin, show increases in both daily doses and duration of use, especially among older adults. Although these trends remain within normal therapeutic ranges, they highlight the need for careful and vigilant prescribing practices.